From 'selective two-child policy' to universal two-child policy: Will the payment crisis of China's pension system be solved? - Yi Zeng; Xinjie Zhang; Lingchen Liu (China Finance and Economic Review, 2017)
Background: With the rapid population aging, the payment crisis of China's pension insurance fund is increasing yearly. The government adjusts fertility policy to alleviate population aging and improve the solvency of pension insurance fund. On January 1, 2016, China's fertility policy was adjusted from 'selective two-child policy' to universal two-child policy. Methods: This paper establishes actuarial models to analyze how fertility policy adjustment influences the pension insurance fund. Results: (1) if the 'one-child policy' were still employed, the accumulated deficit of pension insurance fund would appear in the year of 2076; (2) if all couples that satisfy the rules of 'selective two-child policy' bear the second child, the time of accumulated deficit of pension insurance fund would be postponed by about 9 years; (3) after implementing the universal two-child policy, the time of accumulated deficit of pension insurance fund would delay under different situations of fertility intentions, if more than 54% of the qualified couples bear a second child, the accumulated deficit of pension insurance fund would not appear before 2090. The above conclusions have passed the sensitivity tests. Conclusion: Therefore, 'two-child policy' can alleviate the payment pressure of pension insurance fund. If the government wants to solve the payment crisis of pension insurance fund, fertility intentions should be improved.
Keywords: 330; Universal two-child policy; Pension insurance fund; Payment crisis; Policy simulation